Development of pulsed laser ablation deposition for synthesis of carbon nanostructure - Liew, Seng Choy (2014)
This thesis describes a development work for anisotropic growth of carbon nanotube. It is of interest to overcome the quenching problem found at substrate that affects the anisotropic behavior of carbon nanostructure. Temperature gradient exists between substrate and target hinders the initiation of vapor-liquid-solid (VLS) mechanism. Therefore, in this work, a suitable condition for plume formation is required to be developed first. Quality of vacuum pressure contained as well as regulating the vacuum pressure with Ar gas during pulsed laser ablation deposition (PLAD) process was address. Followed by accurate scanning of laser spot at target through the use of U-clamp designed and located at the target base. Movement of the laser spot was achieved through the wheel and axle in driving the primary focusing lens. Identification of all parameters required for vertically aligned growth of carbon nanostructure from Si wafer substrate was through literature review. A resistive heating plate designed capable heat up to 900 °C over an area of 3 cm by 1.5 cm to address the heat loss issue at substrate site during PLAD process. Al barrier layer of 30 nm thin was deposited using thermal evaporator onto n-type Si wafer as substrate with Miller indices (100). Ablation time of 20 minutes was found best for its minimal amount of amorphous carbon formed at heated substrate characterized using scanning electron microscope (SEM). Those information were used to synthesize vertically aligned carbon nanostructure by using Fe(III) catalyst synthesized using combustion method. Fast reaction of combustion method allows very pure catalyst synthesized with diameter less than 30 nm initially deposited at substrate characterized using transmission electron microscope (TEM). Optimum pressure that prevented the formation of fringes at substrate during the first step of catalyst ablation was at 0.6 torr. Follow by graphite target ablation required 2.5 torr of background pressure for substrate heated at 300 °C and above without fringe formation. Substrate temperature at 500 °C managed to burn off majority of amorphous carbon formed. Bundles of vertically aligned carbon nanotube were observed during TEM characterization. The overall tube diameter was estimated using ImageJ to be less than 20 nm. Encapsulation of catalyst in the carbon nanotube produced confirmed using energy dispersive X-ray (EDX). The system developed managed to synthesis bundles of vertically aligned carbon nanostructure.